Training Program on Developing PowerPoint-Based Interactive Media for Arabic Language Teachers Alumni of Program Profesi Guru (PPG) at Universitas Negeri Malang - Ahsanuddin, Mohammad; Moch. Wahib Dariyadi; Moh. Fery Fauzi; Moh. Sahru Romadhon; Ilvina Maulidiyah Mahmudah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This article examines a training program focused on creating PowerPoint-based interactive media, aimed at Arabic language teachers who are alumni of the Teacher Professional Education Program (PPG) at Universitas Negeri Malang. The main goal of the training was to improve the professional and technological skills of teachers in creating engaging and interactive educational media. The training approach included theoretical instruction, practical exercises, and assessments of participants’ outputs. The findings reveal that participants successfully developed interactive media that were both informative and engaging for students. Additionally, feedback from participants indicated a boost in their confidence in integrating technology into their teaching practices. As a result, the training is anticipated to positively impact the professional development of Arabic language teachers and enhance the overall learning experience in schools. The study also highlights the need for continued training and ongoing support to ensure the effective use of interactive media in educational settings.